The language acceptability of Indonesian Omnibus Law: A structural approach - Hendrastuti, Retno; Okitasari, Indah; Lestariningsih, Dewi Nastiti; Utami, Rini Esti; Maemunah, Emma (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2024)
Linguistically legal text is considered problematic and needs to be assessed whether it can be understood easily by the users or not. This research was a qualitative descriptive that wants to know the assessment of the level of acceptance of law texts from language teachers’ perspective. The data sources consisted of ten articles of Indonesia Job Creation Law 2020, which were examined from the language accuracy (orthography, diction, sentence structure) and informant assessments. The data were collected through observation and questionnaire. The research adapts content analysis techniques that employs four stages, i.e., 1) domain analysis, 2) taxonomy analysis, 3) componential analysis, and 4) cultural theme analysis. The results showed that the assessments of informants showed a relatively high level of acceptance, that was 2.64. Then, there were some language errors that can be used as an object of Indonesian language learning. In orthography some errors were found in the use of periods, colons, hyphens, and word writing. In terms of diction, errors are found in inappropriate words, that was in terms of sebagaimana ‘as’ and dalam hal ‘in terms of’. In sentence structure errors are found in accuracy, clarity, and coherency. It indicates the potency of law texts to be more accessible and ensures its efficient implementation, fostering trust and compliance among the public and legal community.